The Influence of Service Quality and Customer Value on Customer Satisfaction at PT. KONSUIL Pringsewu Area from an Islamic Economics Perspective - Suntiaji Yudho Negoro; Finny Ligery; Ahmad Muklisin; Subandi (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The development of the electrical inspection service sector in Indonesia, particularly PT. KONSUIL as a Technical Inspection Institution issuing Electrical Operation Eligibility Certificates for electrical installations, still faces challenges in service aspects. This condition potentially reduces consumer value and user satisfaction, and creates inconsistency with Islamic economic principles. This study aims to analyze the influence of service quality and consumer value on customer satisfaction of PT. KONSUIL Pringsewu Area from an Islamic economics perspective. This research employs an explanatory quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The population consisted of housewives who used PT. KONSUIL services, totaling 257 individuals, with a sample of 155 respondents selected through purposive sampling based on the criteria of residing in Pringsewu and having used the service at least once. Data were collected through questionnaires. The findings indicate that service quality and consumer value have a positive and significant influence on customer satisfaction, both partially and simultaneously. These results emphasize the importance of integrating service quality and consumer value in building sustainable satisfaction. Strengthening the complaint handling system, fostering a culture of trustworthiness, and implementing service differentiation strategies are key factors in improving service quality and consumer value in accordance with Islamic economic principles.